HYBRID WARFARE CHALLENGES FOR UNITED STATE’S FORCES IN SOUTH ASIA:A CRITICAL ANALYSIS OF THE US-MIDDLE EAST NEXUS SINCE OCTOBER 2023 till 2025 (Contemporary Journal of Social Science Review, 2025)
This paper will discuss the changing challenges of hybrid warfare that the US forces face in South Asia, and especially the interrelation of the Middle East conflict and South Asian security dynamics since October 2023. With the help of the qualitative analysis of secondary sources published by policy think tanks and military institutes, the research answers three research questions: How has the US-Middle East nexus affected the dynamic of hybrid warfare in South Asia? What are the new challenges in the region to the US forces? What are some of the strategic adjustments needed? The analysis indicates that Iranian weakening of the region has ironically increased realignments such as Saudi-Pakistan mutual defence pact whereas the US strategic ambiguity has provided room to the other security structures. The major findings are that the US forces are faced by hybrid threats that include proxy warfare, information operations and the evolving alliance frameworks. The article ends by making policy suggestions on the need to engage in calibrated fashion, intelligence cooperation and the need to acknowledge the role of the South Asian agency in security arrangement.